Assessing potential viral transmission between honeybees and hive-infesting ants using novel per-hive co-detection indices - Rivas Fontan, Ignacio (2025)
Understanding which ant species interacting with honeybees can transmit or acquire viruses is crucial for managing honeybee health. Our objective was to develop a new methodology using two indices, based on a per-hive approach, to identify ant-virus combinations with high transmission potential (Matching Index) and to assess the relative risk posed to honeybees (Risk-to-Bee Index). Our survey in apiaries in Buenos Aires Province, Argentina, revealed that honeybee hives more infested by ants had smaller colonies. The Argentine ant, Linepithema humile, was among the top three ant species infesting hives. Ant brood and queens showed higher virus detection rates compared to workers, increasing virus prevalence in ants. Four viruses were detected in L. humile, but only deformed wing virus (DWV) was more prevalent in honeybees in hives with L. humile. Argentine ants tested negative for chronic bee paralysis virus, which was common in Camponotus species. In our study, per-hive indices suggest that Argentine ants would transmit DWV and black queen cell virus to honeybees, while honeybees would transmit DWV and acute bee paralysis virus to Argentine ants and Camponotus mus. Importantly, although our indices are simpler than previous tools to evaluate interspecific virus transmission, they do not provide definitive conclusions. However, the suggestions they offered align with all existing empirical data, highlighting their robustness. Thus, this approach provides a novel tool for prioritizing research on high-risk virus transmission between honeybees and ants, emphasizing its potential impact on honeybee management.